Pengaruh Profitabilitas Dan Corporate Social Responsibility Disclosure Terhadap Agresivitas Pajak (Studi Empiris Pada Perusahaan Sektor Barang Konsumen Primer yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2020) - Riana, Aista Wahyu; Purwanti, Lilik (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to examine the effect of profitability with ROA, ROE, and Corporate Social Responsibility Disclosure on tax aggressiveness. The data used is secondary data obtained from the official website of the Indonesia Stock Exchange and the official website of each company. The population of this study is the primary consumer goods sector companies listed on the Indonesia Stock Exchange in 2017-2020. The sample used as many as 30 companies for 4 periods selected by purposive sampling method. The results of this study indicate that the ROA and ROE variables are not empirically proven to affect the level of tax aggressiveness so the level of ROA and ROE in a company is not able to control management in minimizing tax aggressiveness actions. Tax aggressiveness can be reduced by increasing Corporate Social Responsibility Disclosure. Abstract This study aims to examine the effect of profitability with ROA, ROE, and Corporate Social Responsibility Disclosure on tax aggressiveness. The data used is secondary data obtained from the official website of the Indonesia Stock Exchange and the official website of each company. The population of this study is the primary consumer goods sector companies listed on the Indonesia Stock Exchange in 2017-2020. The sample used as many as 30 companies for 4 periods selected by purposive sampling method. The results of this study indicate that the ROA and ROE variables are not empirically proven to affect the level of tax aggressiveness, so that the level of ROA and ROE in a company is not able to control management in minimizing tax aggressiveness actions. Tax aggressiveness can be reduced by increasing Corporate Social Responsibility Disclosure.